HISTORY OF RECURRENT UNINTENDED PREGNANCY IN THE UTERINE SCAR AFTER CESAREAN SECTION SURGERY - Эльвира Константиновна Гребенникова; Виталий Борисович Цхай; Ирина Сергеевна Брехова; Марина Яковлевна Домрачева (Мать и дитя в Кузбассе)
In the literature of recent years, special attention has been paid to the form of ectopic localization of the fetal egg - pregnancy in the uterine scar after cesarean section. The steady increase in the number of patients with a history of even one cesarean section operation leads to an increase in the frequency of this form of ectopic pregnancy as pregnancy in the scar.